2008
DOI: 10.1007/s00216-008-2497-7
|View full text |Cite
|
Sign up to set email alerts
|

Development of a nondestructive method for underglaze painted tiles—demonstrated by the analysis of Persian objects from the nineteenth century

Abstract: The paper presents an analytical method developed for the nondestructive study of nineteenth-century Persian polychrome underglaze painted tiles. As an example, 9 tiles from French and German museum collections were investigated. Before this work was undertaken little was known about the materials used in pottery at that time, although the broad range of colors and shades, together with their brilliant glazes, made these objects stand out when compared with Iranian ceramics of the preceding periods and suggest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
11
0
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(15 citation statements)
references
References 20 publications
3
11
0
1
Order By: Relevance
“…The trace of this old-fashioned nanotechnology nowadays can be seen in many museums and historical sites worldwide in the form of colorful tiles [2], lusters [3], glasses [4], etc. The real origin of the coloration was unknown up to the early 20 th century, when theoretical studies shed light into this uncovered optical phenomena [5] which is known today as plasmonics [6] (photon-electron coupling).…”
Section: Introductionmentioning
confidence: 99%
“…The trace of this old-fashioned nanotechnology nowadays can be seen in many museums and historical sites worldwide in the form of colorful tiles [2], lusters [3], glasses [4], etc. The real origin of the coloration was unknown up to the early 20 th century, when theoretical studies shed light into this uncovered optical phenomena [5] which is known today as plasmonics [6] (photon-electron coupling).…”
Section: Introductionmentioning
confidence: 99%
“…The spectroscopic examination of these tiles from British collections revealed a similar range of colorants to those characterised in nineteenth century Persian tiles from German and French collections, which were part of a previous research project (Reiche et al 2009). The spectroscopic examination of these tiles from British collections revealed a similar range of colorants to those characterised in nineteenth century Persian tiles from German and French collections, which were part of a previous research project (Reiche et al 2009).…”
Section: Results Of Fibre Optic Visible Reflectance Spectroscopymentioning
confidence: 58%
“…The present research demonstrated the use of colorants and mixtures that were not employed by Persian potters in the previous centuries (Reiche et al 2009). The present research demonstrated the use of colorants and mixtures that were not employed by Persian potters in the previous centuries (Reiche et al 2009).…”
Section: Discussionmentioning
confidence: 54%
See 1 more Smart Citation
“…Moreover, RBS provides depth-resolved information on the elemental distribution of heavy elements in a light matrix allowing the determination of the thickness of the gold leaves used in the gilding process and the method of application. Ion beam analysis (IBA) techniques implemented with an external beam have been largely exploited for the study of heterogeneous cultural heritage objects for many years because they are non-invasive and can be performed in air [5,6,[15][16][17].…”
Section: Introductionmentioning
confidence: 99%